MCAT 528 : advanced prep for advanced students - Pooran-Kublall, Deeangelee; Kaplan Test Prep and Admissions (2016)
"Covers the topics that our MCAT experts voted as the most challenging and capable of yielding the most points on Test Day, distills the exam's content blueprint so that you know exactly what to study, presents expanded expert explanations highlighting key concepts and takeaways, promotes expertise on the Critical Analysis and Reasoning Skills section by demonstrating parallelism in questions, and provides practice tailored to students looking to test themselves at the highest level."--
Unit 1: MCAT basics and test strategy -- About the MCAT -- Reading the Kaplan way -- Kaplan's question and answer strategies -- Unit 2: Scientific inquiry and reasoning skills -- Skills 1 and 2 -- Skill 3 -- Skill 4 -- Unit 3: Science subject review. Science unit overview -- Behavioral sciences -- Biochemistry -- Biology -- General chemistry -- Organic chemistry -- Physics -- Unit 4: Critical analysis and reasoning skills -- Arguments and formal logic -- CARS question types -- Reasoning within passages.
Keywords: Medical College Admission Test -- Study guides; Medical colleges -- United States -- Entrance examinations -- Study guides; Medicine -- Examinations -- Study guides; Medical College Admission Test; Medical colleges -- Entrance examinations; Medicine -- Examinations; Medical College Admission Test -- Study guides; Medical colleges -- United States; Medicine -- Examinations -- Study guides; United States; Examination Questions; Study guides